What's New After NICE Acne Guidelines - Alison M. Layton; Girish Gupta; Daron Seukeran; Thivi Maruthappu; Stephanie Gaillard; Heather Whitehouse; Faisal R. Ali; Angelika Razzaque; Firas Al-Niaimi; Sarah Copperwheat (Adis, Springer Healthcare, 2024)
Abstract Introduction Acne remains one of the most common inflammatory dermatoses seen worldwide. There are significant challenges when managing acne relating to a variety of factors, including (1) lack of consensus on the use of the numerous available grading systems and outcome measures, (2) appreciation of the numerous areas that relate to severity, (3) the chronic nature of acne which requires a longitudinal approach to management (including both facial and truncal disease), and (4) the need to target acne early to avoid physical and psychosocial scarring. Consideration of these aspects when managing acne should result in improved outcomes. Acne guidelines review the available evidence based on robust clinical trials and are usually supplemented with some expert opinion when evidence is not available. Methods In this paper, the UK Acne Working Group reflects on the latest National Institute for Health and Care Excellence (NICE) acne guidelines with a goal of providing additional practical insights. Conclusion The group have identified areas where new evidence has now become available since the formulation of the NICE acne guidelines. This publication considers newly approved acne medications in the UK, guidance on assessing acne severity, approaches to managing truncal acne, acne sequelae, and adult female acne with hormonal therapies.